Sonata Theory, Secondary Themes and Continuous Expositions: Dialogues with Form‐Functional Theory. (1st February 2016) - HEPOKOSKI, JAMES A.
ABSTRACT: With regard to the definition of secondary (or subordinate) themes within Classical‐style expositions, Sonata Theory and form‐functional theory proceed from different understandings of the style, role and structural purpose of such themes. From the more integrative standpoint of Sonata Theory, the form‐functional understanding, while logically tight, is insufficiently attentive to rhetorical, punctuational and thematic factors that also lie at the core of expositional practice in the second half of the eighteenth century. This article updates my thoughts on secondary‐theme definition in this era, underscoring once again the need for flexibility and musical sensitivity in the application of the 'no MC, no S' guideline. Along the way, I outline a broader historical argument to suggest that, beginning around 1750, the strategic introduction of an emphatic medial caesura (or punctuational 'hard break') into the centre of what we now call sonata expositions effectively and immediately divided any such exposition into two separate parts. Each of the two parts is usually subdivisible into two separate action‐zones, resulting in a de facto P TR'{S/C} pattern, each zone of which soon came to call for its own generically appropriate harmonic and thematic/rhetorical treatment. Under the zonal concept of expositional formatting (precipitated by the presence of an MC), the secondary theme is best construed as that characteristic, new theme that marks the post‐MC onset of the second part. Expositions without an interior MC present us with a different situation, one in which it can be counterintuitive – or at least analytically unnecessary – to posit the presence of a subordinate theme in the zonal sense: one need not presume that all mid‐expositional V:PACs are preceded by a subordinate theme. The article also considers how most productively to interpret a transition‐ending dominant‐lock leading to an MC and concludes by discussing how and why it is possible for a transition‐ending V:PAC to articulate an MC that then gives way to the onset of a characteristic secondary theme.